Analysis of the status of the open pit deposits in the Carpathian Mts. (within Małopolska district) in local landuse plans - Mastej, Paweł (My University, 2017)
The project aims to build geodata base for deposits in Carpathian Mts (within Małopolska distr.) and analyse the status of deposit in local landuse plans. Is the presence of deposit was taken into account when establishing LLP, and if yes, what form of land use was adopted in these areas. This work also give us answer, how LLP covered the real land use.
Analiza statusu złóż, eksploatowanych metodą odkrywkową, w Karpatach (w granicach Małopolski) w planach zagospodarowania przestrzennego
Keywords: status; local landuse plans; deposits; Carpathian